Kufahrite, PtPb, a new mineral from Ledyanoy Creek placer, Galmoenan ultramafic complex, Koryak Highlands, Russia. (26th April 2021) - Sidorov, Evgeniy G.; Kutyrev, Anton V.; Zhitova, Elena S.; Agakhanov, Atali A.; Sandimirova, Elena I.; Vymazalova, Anna; Chubarov, Valery M.; Zolotarev, Andrey A.
Abstract: Kufahrite, PtPb, is a new mineral (IMA2020-045) from the Ledyanoy Creek placer, Koryak Highlands, Russia. The mineral was found in isoferroplatinum (Pt3 Fe) grains extracted from a heavy-mineral concentrate, together with tetraferroplatinum (PtFe), tulameenite (Pt2 FeCu), native iridium, hollingworthite (RhAsS) and Cr-rich spinel. Kufahrite occurs as part of alteration rims which are formed together with tetraferroplatinum after isoferroplatinum, or as grains up to 150 μm in size. According to powder X-ray diffraction analyses kufahrite is isotypic to its synthetic analogue, it is hexagonal and crystallises in space group P 63 / mmc adopting the nickeline structure type. Its unit-cell parameters are: a = 4.2492(6) Å; c = 5.486(6) Å; V = 85.78 Å 3 and Z = 2. The calculated density is 14.80 g/cm –3 . The strongest diffraction lines are [ d, Å ( I, %) ( hkl )]: 3.052 (80) (101), 2.197 (100) (102), 2.125 (28) (110), 1.747 (18) (210), 1.528 (35) (202), 1.240 (18) (212) and 0.958 (22) (312). The Vickers hardness is 295 kg/mm 2 (range 262–320, n = 5), corresponding to a Mohs hardness of 4. The empirical formula of kufahrite, calculated from a mean value of 23 electron-microprobe analyses is (Pt0.94 Rh0.04 )Σ0.98 (Pb0.83 Sb0.19 )Σ1.02 . The name (pronounced as [ku fa rait]) honours Fahrid Shakirovitch Kutyev (1943‒1993), a geologist from the Institute of Volcanology of USSR Academy of Sciences, who played a key role in the discovery of the Koryak–Kamchatka Platinum Belt, including the Ledyanoy Creek placer platinum deposit, where the new mineral has been discovered.